Sexual orientation identity disparities in health behaviors, outcomes, and services use among men and women in the United States: a cross-sectional study. - Jackson, Chandra L.; Agénor, Madina.; Johnson, Dayna A.; Austin, S. Bryn.; Kawachi, Ichirō. (Tufts University. Tisch Library., 2019)
Research shows that sexual minorities (e.g., lesbian, gay, and bisexual individuals) experience higher levels of discrimination, stigma, and stress and are at higher risk of some poor health outcomes and health behaviors compared to their heterosexual counterparts. However, the majority of studies have examined sexual orientation disparities in a narrow range of health outcomes and behaviors using convenience samples comprised of either men or women living in restricted geographic areas.